2009
DOI: 10.1590/s0100-40422009000100016
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de cinza do bagaço de cana-de-açúcar para emprego como pozolana em materiais cimentícios

Abstract: Recebido em 10/1/08; aceito em 23/7/08; publicado na web em 20/1/09 CHARACTERIZATION OF SUGAR CANE BAGASSE ASH FOR USE AS POZZOLAN IN CEMENTITIOUS MATERIALS.This work presents the results of morphological and physical-chemical characteristics of a sugar cane bagasse ash material sample produced under controlled burning conditions. The investigation was carried out by analyzing chemical composition, X-ray diffraction, 29Si nuclear magnetic resonance, morphology, thermal analysis, particle size, specific surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 7 publications
(12 reference statements)
2
16
0
21
Order By: Relevance
“…This burning approach was established in function of the TGA of SCS samples. A similar burning procedure was previously used to produce ashes containing high amorphous silica and low loss on ignition from sugar cane bagasse 11,16 and elephant grass. 23 The ashes produced from burning of IN-SCS, WW-SCS, and HL-SCS were denominated IN-SCSA, WW-SCSA, and HL-SCSA, respectively.…”
Section: Pretreatment Of Straw Samples and Production Of Ashesmentioning
confidence: 99%
See 1 more Smart Citation
“…This burning approach was established in function of the TGA of SCS samples. A similar burning procedure was previously used to produce ashes containing high amorphous silica and low loss on ignition from sugar cane bagasse 11,16 and elephant grass. 23 The ashes produced from burning of IN-SCS, WW-SCS, and HL-SCS were denominated IN-SCSA, WW-SCSA, and HL-SCSA, respectively.…”
Section: Pretreatment Of Straw Samples and Production Of Ashesmentioning
confidence: 99%
“…Previous studies have shown that the pozzolanic potential of SCBA may be improved by controlled calcination 11,14,16 and mechanical grinding 9,17,18 processes. Moreover, different studies have shown that the pozzolanic properties of RHA may be strongly enhanced through prior acid leaching of husk.…”
Section: Introductionmentioning
confidence: 99%
“…Cordeiro et al 10,16 showed that burning ashes between 400°C and 600°C produces an increase in the pozzolanic activity index with increasing firing temperatures due to the loss of carbon during the calcination process. According to these authors, the formation of crystalline silica compounds is observed at a firing temperature of 800°C, causing a drop in the pozzolanic activity index at that temperature.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Dentre os tipos de sílica disponíveis no mercado, encontra-se o Aerosil ® , empregado em diferentes produtos comerciais usado em áreas de alta tecnologia, devido sua elevada pureza (> 99% em massa de SiO 2 ). Desse modo, a sílica gel se sobressai como um sólido poroso dotado de propriedades químicas e físicas específicas, podendo ser usada como matéria prima para fabricação de zeólitas [21], MCM [22], refratários [23], materiais de construção civil [24], pozolânicos [25], argamassa [26], entre outros. Quando sua superfície é quimicamente modificada por um agente organofuncionalizante [27], a sílica pode ser usada como suporte para catalisadores [28], fase estacionária em cromatografia líquida de alta eficiência (CLAE) [29] e para liberação controlada de fármacos [30], em tecnologias fotodinâmicas nas terapias do câncer [31] ou ainda como agente sequestrante de metais [32].…”
Section: Introductionunclassified